Progress of research on distribution and function of bitter taste receptors in oral cavity - ZHANG Xiaojie, LIU Nan, XU Zimo, ZHANG Cui, QIN Qing, ZHU Kang, REN Xiaoyong, CHEN Jingguo (Editorial Office of Stomatology, 2024)
Recent studies have demonstrated that bitter taste receptors are distributed not only in oral cavity but also in non-gustatory systems, such as the respiratory, digestive, reproductive and cardiovascular systems. The physiological role of bitter taste receptors is to recognize bitter substances or bacterial secretions, to trigger the immune response and to maintain the internal environmental homeostasis. In addition, oral bitter taste receptors are expressed not only in taste buds, perceiving bitter taste, but also in many other parts of periodontal tissues, which is the potential treatment target for oral infectious diseases. This review summarized the expression and distribution of oral bitter taste receptors which was off the taste buds and their roles in regulating oral inflammation and oral bacteria, discussed the effects of genetic polymorphism of bitter taste receptor 38 subtype(TAS2R38)on innate immunity and its relationship with the susceptibility of dental caries and periodontal, aimed to provide novel ideas for the better prevention and treatment of dental caries and periodontal diseases.